Profil Kemampuan Berpikir Kritis Peserta Didik Kelas VIII Berdasarkan Indikator Ennis di Surabaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the profile of critical thinking skills of eighth-grade students at SMP Surabaya using a test instrument developed based on critical thinking indicators according to Ennis (2011). The study employed a quantitative descriptive approach involving 58 students as the sample. Three out of the five groups of Ennis’s critical thinking indicators measured include: providing simple explanations (MPS), building basic skills (MKD), and making conclusions (MK).The results of the descriptive analysis show that the overall average score of students’ critical thinking skills is 4.73 (SD = 2.57), with the majority of students (64%) categorized as low (poor). Indicator-wise analysis reveals that the average scores for MPS, MKD, and MK are 4.93, 4.91, and 4.34, respectively, indicating that the ability to make conclusions is the weakest aspect.These findings suggest that the critical thinking skills of junior high school students are generally at a low level and require well-planned and systematic instructional interventions, particularly in strengthening inference skills.